Comparison of cardiorespiratory effects and perioperative analgesia efficacy of dexmedetomidine or fentanyl continuous infusion during ovariohysterectomy in propofol-anesthetized dogs (Research, Society and Development, 2023)
The present study aimed to compare the cardiorespiratory, perioperative analgesic and blood gas analysis of the constant rate infusion of dexmedetomidine or fentanyl in 16 female dogs undergoing to elective ovariohysterectomy. The dogs were premedicated with morphine (0.5 mg/kg) and dexmedetomidine (5 µg/kg) or acepromazine (0.05 mg/kg), both intramuscularly (IM), in GDEX or GFEN, respectively. After anesthesia induction with propofol intravenously (IV), animals of GFEN received bolus of fentanyl (2.5 µg/kg) IV followed by continuous rate infusion (CRI) (10 µg/kg/h) and the GDEX received bolus of saline solution 0.9% (corresponding volume of fentanyl) followed by CRI of dexmedetomidine (1 µg/kg/h) and anesthesia was maintained with propofol (0.22 mg/kg/min). In the end of surgery all animals were evaluated using the Glasgow composite measure pain scale (GCPS) and a visual analogue scale (VAS). Data was compared with a statistical p value > 0,05. The mean heart rate was statistically lower in GDEX when compared to GFEN (p = 0.0498): 54.25 ± 3.919 and 88.38 ± 8.766 beats per minute, respectively. Opposed, the average mean blood pressure was statistically higher in GDEX when compared to GFEN (p = 0.0021): 99.38 ± 8.551 and 80.75 ± 11.12 mmHg, respectively. The GDEX and GFEN, in the firsts 4 and 2 postoperative hours, respectively, presented values significantly higher than baseline in the GCPS, occurring analgesic rescues for both groups. It is concluded that both drugs in the proposed rates were safe and efficient for nociceptive control during intraoperative, however, failed to promote efficient postoperative analgesia.